Low-friction high-wear-resistance resin-based composite material as well as preparation method and application thereof

By using inorganic fillers such as graphite and m moy molybdenum, combined with short carbon fiber in the resin -based composite material, combined with short carbon fiber to build a multi -scale function filler network structure, the existing resin base composite material is solved. The problem of insufficient friction performance under high -speed heavy load conditions has achieved the preparation of low friction and high -wear -resistant polyphenylene sulfur ether -based composite materials, which is suitable for areas with high performance needs.

CN119350847AActive Publication Date: 2025-01-24SICHUAN UNIV

Patent Information

Application Number
CN202411637633.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-24
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

Existing resin-based composite materials have insufficient friction performance under high-speed heavy load conditions, making it difficult to meet the high-performance needs in the fields of aerospace and other fields.

Method used

Using radiation-modified polytetrafluoroethylene nanopowder and inorganic fillers such as graphite and molybdenum disulfide at a certain compound ratio, combined with chopped carbon fibers, a multi-scale functional filler network structure is constructed to prepare polyphenylene with low friction and high wear resistance. thioether-based composites.

Benefits of technology

It realizes low friction and high wear resistance under high -speed heavy load, improves the comprehensive performance of materials, and is suitable for aerospace, transportation, and electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350847A_ABST
    Figure CN119350847A_ABST
Patent Text Reader

Abstract

The invention provides a low-friction high-wear-resistance resin-based composite material as well as a preparation method and application thereof, and belongs to the field of composite materials. The polyphenylene sulfide-based composite material is prepared from radiation-modified polytetrafluoroethylene nano-powder, graphite nano-powder, molybdenum disulfide nano-powder and other inorganic filler particles in a certain compounding ratio. The composite material shows excellent tribological performance, and on the basis, by adding short carbon fibers and other reinforcing fillers and utilizing a multi-scale functional filler network structure built in the composite material, preparation of the high-strength, low-friction and high-wear-resistance polyphenylene sulfide-based composite material is achieved. The method is simple in technical process route and low in manufacturing cost, can be used for preparing friction protection parts, low-friction wear-resistant structures, wear-resistant bearings, self-lubricating parts, mechanical gaskets and other parts used under dry friction, and has very wide application prospects in the fields of aerospace, traffic transportation, electronic devices, high-end mechanical equipment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of composite materials, and in particular relates to a low-friction and high-wear-resistant resin-based composite material and a preparation method and application thereof. Background Art

[0002] In recent years, resin-based composite materials have attracted people's attention due to their advantages such as low cost, light weight, and easy processing and molding. They are widely used in aerospace, transportation, military equipment, biomedicine, electronic information and other fields. However, in practical applications, materials often interact with each other continuously. In order to avoid safety accidents and economic losses caused by severe friction and wear between materials, the development of resin-based composite materials with excellent tribological properties has attracted the attention of researchers and material manufacturers. In particular, aerospace vehicles (such as aircraft, rockets and satellites) are often faced with heavy-load and high-speed friction environments under conditions such as high-speed flight, high-speed injection and maneuvering, which not only affects the wear and service life of the components, but also leads to reduced functions or even failure. Therefore, achieving friction protection under high-speed and heavy-load conditions is a key factor in ensuring the efficient, stable and safe operation of the system.

[0003] Special engineering plastics (polyphenylene sulfide, polyetheretherketone, polyimide, etc.) have received extensive attention due to their excellent mechanical properties, chemical corrosion resistance and thermal stability, and have become the most promising polymer materials in the field of tribology. With the development of high-tech, people have put forward more stringent requirements on the friction and wear performance of resin-based composite materials. In the past, many scholars at home and abroad have carried out a lot of research work and explored various ways to prepare resin-based composite materials that can meet higher friction and wear performance requirements.

[0004] For example, the patent application with publication number CN116925547A discloses a low friction coefficient polyphenylene sulfide material and its preparation method. The invention forms a composite phase interface by microscopically coating the surface of polyphenylene sulfide powder particles with polymer gel or polymer-inorganic hybrid gel, and then melts and compounds it with reinforcing agent, lubricant and dispersant at high temperature to form an interface that is more conducive to reducing friction. However, the preparation process is cumbersome, and the mechanical properties of the material are poor, making it difficult to apply under harsh conditions such as high speed and heavy load. The patent application with publication number CN115785671A discloses an aerogel / polyphenylene sulfide self-lubricating friction material and its preparation method. The invention uses aerogel, reinforcing fiber and liquid phase auxiliary agent to mix and fill PPS, but its low thermal conductivity makes the improvement of friction and wear performance unsatisfactory. The patent application with publication number CN112094499A applies for a high thermal conductivity and low friction coefficient polyphenylene sulfide / boron nitride (PPS / BN) composite material and its preparation method. The invention constructs an isolated network structure in which BN micro-sheets are directional distributed between PPS particles by tightly and evenly coating the surface of PPS particles with BN micro-sheets, thereby constructing a BN three-dimensional thermal conductive network structure to reduce heat accumulation during friction, but the degree of improvement in self-lubricating performance is limited (the minimum friction coefficient is 0.180). Therefore, the development of a low-friction and high-wear-resistant resin-based composite material that can meet higher friction and wear performance requirements and has both excellent mechanical strength and high thermal conductivity has important scientific value and application prospects. Summary of the invention

[0005] The object of the present invention is to provide a low-friction and high-wear-resistant resin-based composite material and a preparation method and use thereof.

[0006] The invention provides a low-friction and high-wear-resistant resin-based composite material, which is prepared from the following raw materials in parts by weight: 10 to 200 parts of a resin matrix, 5 to 80 parts of a solid lubricant, and 0 to 60 parts of a reinforcing agent; the solid lubricant is a mixture of polytetrafluoroethylene or its derivatives and a carbon material, or a mixture of polytetrafluoroethylene or its derivatives and a metal derivative.

[0007] Furthermore, it is prepared from the following raw materials in parts by weight: 10 to 200 parts of a resin matrix, 5 to 40 parts of a polytetrafluoroethylene derivative, 5 to 30 parts of a carbon material, and 0 to 60 parts of a reinforcing agent;

[0008] Alternatively, it is prepared from the following raw materials in parts by weight: 10 to 200 parts of a resin matrix, 5 to 40 parts of a polytetrafluoroethylene derivative, 5 to 30 parts of a metal derivative, and 0 to 60 parts of a reinforcing agent.

[0009] Further, the resin matrix is ​​a thermoplastic resin;

[0010] The reinforcing agent is glass fiber, aramid fiber, basalt fiber, or carbon fiber.

[0011] Furthermore, the resin matrix is ​​polyoxymethylene, polyamide, polysulfone, polyphenylene sulfide, polyetheretherketone or polyimide;

[0012] The polytetrafluoroethylene derivative is radiation-modified polytetrafluoroethylene, preferably radiation-modified polytetrafluoroethylene nanopowder;

[0013] The carbon material is graphite, preferably graphite nanopowder;

[0014] The metal derivative is one or a mixture of two or more of metal sulfide, metal oxide, metal nitride and metal carbide, preferably molybdenum disulfide, more preferably molybdenum disulfide nanopowder;

[0015] The reinforcing agent is chopped carbon fiber.

[0016] Furthermore, the low-friction and high-wear-resistant resin-based composite material is prepared from the following raw materials in parts by weight: 50 to 75 parts of a resin matrix, 10 to 30 parts of a polytetrafluoroethylene derivative, 10 to 30 parts of a carbon material, and 0 to 20 parts of chopped carbon fibers;

[0017] Alternatively, the low-friction and high-wear-resistant resin-based composite material is prepared from the following raw materials in parts by weight: 50 to 75 parts of resin matrix, 10 to 30 parts of polytetrafluoroethylene derivatives, 10 to 30 parts of metal derivatives, and 0 to 20 parts of chopped carbon fibers.

[0018] Furthermore, the low-friction and high-wear-resistant resin-based composite material is prepared from the following raw materials in parts by weight: 70 parts of resin matrix, 10 to 20 parts of polytetrafluoroethylene derivatives, and 10 to 20 parts of carbon materials;

[0019] Alternatively, the low-friction and high-wear-resistant resin-based composite material is prepared from the following raw materials in parts by weight: 70 parts of resin matrix, 10-20 parts of polytetrafluoroethylene derivatives, and 10-20 parts of metal derivatives.

[0020] The present invention also provides a method for preparing the above-mentioned low-friction and high-wear-resistant resin-based composite material, the method comprising the following steps: drying the raw materials, mixing, plasticizing, and drying again to obtain the low-friction and high-wear-resistant resin-based composite material. Further, the drying temperature is 60-100°C, the drying time is 8-16 hours; the plasticizing processing temperature is 200°C-350°C; preferably, the drying temperature is 80°C, the time is 12 hours; the plasticizing processing temperature is 280°C-300°C.

[0021] The present invention also provides the use of the low-friction and high-wear-resistant resin-based composite material in aerospace, transportation electronic devices and mechanical equipment.

[0022] Furthermore, the composite material is used to prepare friction protection parts, low-friction wear-resistant structures, wear-resistant bearings, self-lubricating bearings, and parts of mechanical linings.

[0023] Experiments show that the present invention uses radiation-modified polytetrafluoroethylene nanopowder and inorganic filler particles such as graphite nanopowder and molybdenum disulfide nanopowder to prepare polyphenylene sulfide-based composite materials at a certain compounding ratio. The composite material exhibits excellent tribological properties. On this basis, by adding reinforcing fillers such as chopped carbon fibers and utilizing the multi-scale functional filler network structure constructed inside the composite material, a high-strength, low-friction and high-wear-resistant polyphenylene sulfide-based composite material is prepared. The technical process route of the present invention is simple and the manufacturing cost is low. It can be used to prepare friction protection parts, low-friction and wear-resistant structures, wear-resistant bearings, self-lubricating parts, mechanical gaskets and other parts used under dry friction. It has very broad application prospects in the fields of aerospace, transportation, electronic devices and high-end mechanical equipment.

[0024] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.

[0025] The above contents of the present invention are further described in detail below through specific implementation methods in the form of examples. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 FTIR spectrum data of untreated PTFE, i-PTFE, pure PPS and PPS / i-PTFE30 composite material (A) and schematic diagram of the morphology of untreated PTFE and i-PTFE powder (B).

[0027] Figure 2 This is a graph showing the tribological performance data of the PPS-based composite system.

[0028] Figure 3 Schematic diagram of the quenching cross-section morphology of pure PPS (A), PPS / i-PTFE (B) and PPS / m-PTFE (C).

[0029] Figure 4 This is the tensile strength data of the PPS-based composite system.

[0030] Figure 5Schematic diagram of the brittle fracture surface morphology of modified PPS-based composites filled with different solid lubricants.

[0031] Figure 6 The mechanical properties data of PPS-based composites filled with different solid lubricants are shown in Figure 2.

[0032] Figure 7 The instantaneous friction coefficient, average friction coefficient and specific wear rate data of modified PPS-based composites filled with different solid lubricants.

[0033] Figure 8 Schematic diagram and 3D contour diagram of the wear surface morphology of modified PPS-based composites filled with different solid lubricants.

[0034] Fig. 9 The instantaneous friction temperature and thermal conductivity data of modified PPS-based composites filled with different solid lubricants.

[0035] Fig.10 Schematic diagram of EDS elemental analysis of modified PPS-based composites filled with different solid lubricants.

[0036] Fig.11 This is the XPS analysis data of PPS-based composites filled with different solid lubricants.

[0037] Fig.12 This is the mechanical properties analysis data of PPS-based composite materials after adding carbon fiber.

[0038] Fig.13 This is the tribological performance analysis data of PPS-based composite materials after adding carbon fiber.

[0039] Fig.14 It is the instantaneous friction temperature and thermal conductivity of PPS-based composite materials after adding carbon fiber. DETAILED DESCRIPTION

[0040] The raw materials used in the present invention are as follows:

[0041] Polyphenylene sulfide (PPS) was purchased from Deyang Keji High-tech Materials Co., Ltd. with the product model KJ504, and irradiated modified polytetrafluoroethylene nanopowder (i-PTFE, average particle size 200-300nm) was purchased from Sichuan Jinhe Polymer Materials Co., Ltd. with the product model JH-305F; graphite (Gr, average particle size 500nm); molybdenum disulfide (MoS2, average particle size 500nm); short chopped carbon fiber (SCF, average length 3mm).

[0042] Example 1: Preparation of Gr-filled modified PPS-based composite material of the present invention

[0043] Before extrusion granulation, the raw materials were dried in a blast drying oven at 80°C for 12 hours. The materials were mixed in a ratio of 70wt% PPS, 20wt% i-PTFE, and 10wt% Gr, and then melt-mixed in a co-rotating parallel twin-screw extruder at a processing temperature of 280°C-300°C. After being uniformly plasticized by the extruder, cooled and granulated, the materials were placed in a blast drying oven and dried for 12 hours to obtain a Gr-filled modified PPS-based composite material (abbreviated as P / i-PTFE20 / Gr10).

[0044] Example 2: Preparation of Gr-filled modified PPS-based composite material of the present invention

[0045] Before extrusion granulation, the raw materials were dried in a blast drying oven at 80°C for 12 hours. The materials were mixed in a ratio of 70wt% PPS, 20wt% i-PTFE, and 20wt% Gr, and then melt-mixed in a co-rotating parallel twin-screw extruder at a processing temperature of 280°C-300°C. After being uniformly plasticized by the extruder, cooled and granulated, the materials were placed in a blast drying oven and dried for 12 hours to obtain a Gr-filled modified PPS-based composite material (abbreviated as P / i-PTFE20 / Gr20).

[0046] Example 3: Preparation of MoS2-filled modified PPS-based composite material of the present invention

[0047] Refer to the method of Example 1, the only difference is that the materials are weighed in the ratio of 70wt% PPS, 20wt% i-PTFE, and 10wt% MoS2, and processed at a temperature of 280℃-300℃ using a co-rotating parallel twin-screw extruder to obtain a MoS2-filled modified PPS-based composite material (abbreviated as P / i-PTFE20 / MoS210).

[0048] Example 4: Preparation of MoS2-filled modified PPS-based composite material of the present invention

[0049] Refer to the method of Example 1, the only difference is that the materials are weighed in the ratio of 70wt% PPS, 20wt% i-PTFE, and 20wt% MoS2, and processed at a temperature of 280℃-300℃ using a co-rotating parallel twin-screw extruder to obtain a MoS2-filled modified PPS-based composite material (abbreviated as P / i-PTFE20 / MoS220).

[0050] Example 5: Preparation of SCF and Gr-filled modified PPS-based composite material of the present invention

[0051] Refer to the method of Example 1, the only difference is that the materials are weighed in a ratio of 56wt% PPS, 16wt% i-PTFE, 8wt% Gr, and 20wt% SCF, and processed at a temperature of 280°C-300°C using a co-rotating parallel twin-screw extruder to obtain an SCF and Gr filled modified PPS-based composite material (referred to as P / i-PTFE / Gr / SCF).

[0052] Example 6: Preparation of SCF and MoS2-filled modified PPS-based composite material of the present invention

[0053] Refer to the method of Example 1, the only difference is that the materials are weighed in the proportion of 56wt% PPS, 16wt% i-PTFE, 8wt% MoS2, and 20wt% SCF, and processed at a temperature of 280℃-300℃ using a co-rotating parallel twin-screw extruder to obtain an SCF and MoS2 filled modified PPS-based composite material (referred to as P / i-PTFE / MoS2 / SCF).

[0054] The following is a control sample preparation.

[0055] Comparative Example 1: Preparation of unmodified PPS-based material of the present invention

[0056] Before extrusion granulation, the raw materials are dried in a blast drying oven at 80°C for 12 hours. After the materials are mixed in a ratio of 100wt% PPS, they are melt-mixed in a co-rotating parallel twin-screw extruder at a processing temperature of 280°C-300°C. After being uniformly plasticized by the extruder, cooled and granulated, they are placed in a blast drying oven and dried for 12 hours to obtain an unmodified PPS-based material (referred to as PPS).

[0057] Comparative Example 2: Preparation of the i-PTFE-modified PPS-based composite material of the present invention

[0058] Referring to the method of Control Example 1, the only difference is that the materials are weighed in a ratio of 70wt% PPS and 30wt% i-PTFE, and processed at a temperature of 280°C-300°C using a co-rotating parallel twin-screw extruder to obtain an i-PTFE-modified PPS-based composite material (referred to as P / i-PTFE30).

[0059] Comparative Example 3: Preparation of Gr-modified PPS-based composite material of the present invention

[0060] Referring to the method of Control Example 1, the only difference is that the materials are weighed in a ratio of 70wt% PPS and 30wt% Gr, and processed at a temperature of 280°C-300°C using a co-rotating parallel twin-screw extruder to obtain a Gr-modified PPS-based composite material (abbreviated as P / Gr30).

[0061] Comparative Example 4: Preparation of MoS2-modified PPS-based composite materials of the present invention

[0062] Referring to the method of Control Example 1, the only difference is that the materials are weighed in a ratio of 70wt% PPS and 30wt% MoS2, and processed at a temperature of 280°C-300°C using a co-rotating parallel twin-screw extruder to obtain a MoS2-modified PPS-based composite material (referred to as P / MoS230 for short).

[0063] Table 1 The proportion and number of each group of PPS-based composite materials of Examples 1 to 6 and Comparative Examples 1 to 4

[0064]

[0065] The beneficial effects of the present invention are demonstrated by experimental examples below.

[0066] Experimental Example 1: Structural Characterization and Performance Testing of Radiation-modified Polytetrafluoroethylene Nanopowder

[0067] (1) Structural characterization

[0068] Figure 1 A shows the FTIR spectra of untreated PTFE and i-PTFE powders, pure PPS and PPS / i-PTFE20. -1 The characteristic absorption peaks observed at 1227 and 1152 cm-1 are attributed to the presence of -CF2 groups, while -1 The peaks at 634 and 502 cm are related to the symmetric stretching vibration and antisymmetric stretching vibration of the -CF2 group, respectively. -1 The absorption peak at 994 cm belongs to the bending vibration of the -CF2 group. -1 The absorption peak corresponds to the -CF3 group. The above results show that the characteristic absorption peaks of PTFE are observed in both types of fillers. However, there are slight differences between the FTIR spectra of the two fillers. For example, at 3498 and 870 cm -1 The characteristic absorption peaks detected at 1796 cm-1 are attributed to the stretching vibration and out-of-plane bending vibration of -OH. -1The absorption peak is related to the stretching vibration of C=O. When PTFE was irradiated under air conditions, functional groups such as -COF / -COOH were generated on the PTFE surface. In short, the irradiation energy generated a large number of fluorine-containing free radicals (-CF2·) by inducing PTFE chain scission. Then, O2 in the air diffused and reacted with the fluorine-containing free radicals to generate -COF. Afterwards, under the action of H2O, -COF hydrolyzed to form -COOH groups. Therefore, it can be concluded that oxygen-containing groups such as -OH and C=O were introduced on the surface of PTFE powder due to irradiation treatment. In addition, in addition to the characteristic absorption peak of PPS, the -COOH absorption peak was also detected in the FTIR spectrum of PPS / i-PTFE20, which indicates that the melt processing technology has little effect on the surface properties of i-PTFE powder.

[0069] Figure 1 B shows the morphology of the unirradiated PTFE and i-PTFE powders. After irradiation, the average particle size of the PTFE powder decreased from about 300 nm to about 200 nm. In addition, the untreated PTFE showed more severe agglomeration compared to the i-PTFE. In addition, the fibrous structure observed in the original unirradiated PTFE was not present in the i-PTFE, which was mainly attributed to the degradation effect caused by the irradiation treatment.

[0070] (2) Performance testing

[0071] Combined with the tribological properties of the PPS-based composite system ( Figure 2 ), quenching cross-section morphology ( Figure 3 (A) pure PPS; (B) PPS / i-PTFE; (C) PPS / m-PTFE) and tensile strength of PPS-based composites ( Figure 4 ) data analysis shows that radiation treatment of i-PTFE can significantly improve the compatibility of fillers and matrix, optimize the dispersion of fillers in the matrix, which is beneficial to the formation of high-quality lubricating transfer film during the friction process, exert a better wear-reducing effect, and effectively reduce the adverse effects of fillers on the mechanical properties of composite materials.

[0072] From the above experimental results, it can be seen that the surface polarity of the irradiated modified polytetrafluoroethylene nanopowder increases, thereby improving its interfacial bonding with the PPS matrix. Compared with the unmodified polytetrafluoroethylene powder, it shows great advantages in improving the tribological and mechanical properties of the composite material.

[0073] Experimental Example 2: Performance test of samples

[0074] According to the requirements of the tribological test and the mechanical property test strips, the samples obtained in Examples 1 to 6 and Control Examples 1 to 4 were injection molded on a servo injection molding machine, wherein the temperatures of each zone of the injection molding machine were: 220-320°C for the front section of the barrel, 250-350°C for the middle section of the barrel, and 250-350°C for the rear section of the barrel; the injection pressure was 120 MPa, and the injection speed was 35-45 g / s.

[0075] 1. Experimental methods

[0076] (1) Mechanical properties test: dumbbell-shaped specimens were prepared according to GB / T 1040.2-2022 and the tensile properties were tested. The specimen size was: 150×10×4 mm 3 , the test rate is 10mm / min; according to GB / T9341-2008, a rectangular specimen is made and the bending performance is tested. The specimen size is: 80×10×4mm 3 , the test rate is 2mm / min.

[0077] (2) Friction and wear test: According to GB / T 3960-2016 standard, the tribological properties of PPS-based composite materials were tested using an M-200 ring-block friction and wear tester. Sample size: 30mm*7mm*6mm. A titanium alloy ring was used as the friction pair, with an outer diameter of 40mm and a surface roughness (Ra): 0.7-0.9μm. Before the test, the surface of the friction pair was polished with sandpaper and ultrasonically cleaned in acetone. Sliding speed: 0.42m / s, load: 200N.

[0078] (3) The quenched section, worn surface and corresponding friction pair surface morphology of the sample were observed by scanning electron microscope, and the composition and distribution of elements on the quenched section and corresponding friction pair surface of the sample were investigated by energy dispersive X-ray spectrometer equipped with the system. The chemical state and composition of elements on the worn surface of the sample were investigated by X-ray photoelectron spectrometer, and the test voltage and current were 10kV and 7mA respectively. The wear scar of the sample was characterized by 3D profile measuring instrument, the wear condition of the sample was observed and the related profile parameters were determined. The Shore D hardness of PPS composite material was tested in accordance with GB / T2411-2008 under the maximum load of 50N by HANDPILX-D Shore hardness tester. The thermal conductivity of the sample was measured by Hot Disk thermal constant analyzer by transient heat source method. The sample was placed on the upper and lower surfaces of the thermal conductivity probe and compacted, and the thermal conductivity was calculated by measuring the temperature change of the sample under the action of the heat source.

[0079] 2. Experimental results

[0080] (1) Performance test results of composite materials without carbon fiber

[0081] like Figure 5 As shown in the figure, the internal structure of the modified PPS composite filled with granular filler (i-PTFE) and layered filler (Gr, MoS2) presents different microscopic morphologies as their content ratios vary. The former tends to agglomerate or form voids, while the latter tends to tear under the action of external forces and tends to form a morphology in which the fillers are closely stacked.

[0082] like Figure 6 As shown in the figure, the addition of Gr and MoS2 can improve the bending and shear deformation resistance of PPS, and the tensile strength of the composite material is reduced. The addition of i-PTFE particles also weakens the mechanical properties of PPS to a certain extent.

[0083] like Figure 7 As shown, i-PTFE particles alone can effectively improve the tribological properties of PPS, and Gr or MoS2 alone can also effectively improve the tribological properties of PPS. Further comparison found that when PPS was 70wt%, the tribological properties of P / i-PTFE20 / Gr10 and P / i-PTFE10 / Gr20 were better than those of P / i-PTFE30 and P / Gr30, indicating that Gr and i-PTFE co-filled at a certain compounding ratio produced a synergistic effect. Similarly, when PPS was 70wt%, the tribological properties of P / i-PTFE20 / MoS2 10 and P / i-PTFE10 / MoS2 20 were better than those of P / i-PTFE30 and P / MoS2 30, indicating that MoS2 and i-PTFE co-filled at a certain compounding ratio produced a synergistic effect.

[0084] Further comparison of the tribological properties of P / i-PTFE20 / Gr10 and P / i-PTFE10 / Gr20 revealed that P / i-PTFE20 / Gr10 was superior, indicating that the synergistic effect of Gr and i-PTFE at this compounding ratio was better. Similarly, comparison of the tribological properties of P / i-PTFE20 / MoS2 10 and P / i-PTFE10 / MoS2 20 revealed that P / i-PTFE20 / MoS2 10 was superior, indicating that the synergistic effect of MoS2 and i-PTFE at this compounding ratio was better.

[0085] like Figure 8As shown in the figure, pure PPS suffers from severe rolling damage and large wear marks after wear. In addition, the addition of MoS2 or Gr alone causes severe wear of PPS. It can be seen from the important parameters of the wear marks of PPS-based composite materials (see Table 2) that the addition of i-PTFE, with its excellent self-lubricating properties, can greatly improve the tribological properties of PPS, but due to the poor mechanical strength of the material, it still produces large wear; further, it is observed that the wear degree of P / i-PTFE20 / Gr10 and P / i-PTFE20 / MoS2 10 composite materials is smaller, and the wear surface is smoother. Both composite materials show excellent tribological modification effects, which shows that i-PTFE and Gr or MoS2 will produce a certain synergistic effect at a certain ratio, thereby achieving a significant improvement in the tribological properties of the composite material and improving the friction reduction and wear reduction performance of the material.

[0086] Table 2. Important parameters of wear scar of PPS-based composites

[0087]

[0088] like Fig. 9 As shown in the figure, due to the severe friction and wear, a large amount of friction heat is generated and seriously accumulated between the matrix and the contact interface, which in turn causes the softening deformation and melting degradation of the polymer matrix, resulting in poor tribological properties of the material. The addition of Gr provides excellent thermal conductivity, while MoS2 has a smaller effect on thermal conductivity. However, both PPS / i-PTFE / Gr and PPS / i-PTFE / MoS2 show lower friction temperatures, which indicates that the mechanisms of the two fillers in improving the tribological properties of PPS are not exactly the same.

[0089] like Fig.10 As shown in the figure, the transfer film composed of different materials on the friction pair surface has different degrees of improvement, including PPS matrix, Gr, i-PTFE and MoS2, as well as materials produced by tribochemical reactions between them, which have a certain impact on the combination of metal friction pair and transfer film. Among them, MoS2 shows good tribological properties with metal friction pair.

[0090] Fig.11 The full XPS spectrum of the composite material wear surface. The results show that P / i-PTFE20 / Gr10 mainly plays a self-lubricating role through substances containing C and F, and no special friction chemical reaction occurs. The P / i-PTFE20 / MoS2 10 composite material has a Mo 3d energy spectrum peak, and has a higher S ratio and a lower F ratio, indicating that MoS2 plays an important role in reducing friction and wear. Both P / i-PTFE20 / Gr10 and P / i-PTFE20 / MoS2 10 show excellent tribological properties.

[0091] (2) Performance test results of carbon fiber composite materials

[0092] Further, in PPS / i-PTFE20 / Gr10 (P / i-PTFE / Gr) and

[0093] Reinforced carbon fibers were introduced into PPS / i-PTFE20 / MoS210 (P / i-PTFE / MoS2), and the mechanical and tribological properties of the resulting composite materials were investigated.

[0094] Fig.12 It shows that with the introduction of 20wt% carbon fiber, the mechanical properties of P / i-PTFE / Gr and P / i-PTFE / MoS2 are significantly improved.

[0095] Fig.13 It shows that with the filling of 20wt% carbon fiber, the friction coefficients of P / i-PTFE / Gr and P / i-PTFE / MoS2 are reduced to a certain extent.

[0096] Fig.14 It shows that with the addition of 20wt% carbon fiber, P / i-PTFE / Gr exhibits a lower instantaneous friction temperature during the friction process. Combined with the high thermal conductivity of P / i-PTFE / Gr / SCF, P / i-PTFE / Gr / SCF exhibits excellent friction and wear performance during the friction process. While P / i-PTFE / MoS2 has an improved thermal conductivity after the addition of carbon fiber, the instantaneous temperature during the friction process does not show a significant decrease.

[0097] From the above experimental results, it can be seen that the radiation-modified polytetrafluoroethylene is mixed with graphite, molybdenum disulfide and carbon fiber in a certain compounding ratio, and a multi-scale functional filler network structure is constructed inside the composite material, so that the composite material exhibits the best comprehensive performance, and the preparation of a high-strength, low-friction and wear-resistant polyphenylene sulfide-based composite material is achieved.

[0098] In summary, the present invention provides a low-friction and high-wear-resistant resin-based composite material and a preparation method thereof. The present invention uses radiation-modified polytetrafluoroethylene powder and graphite and molybdenum disulfide in a certain compounding ratio to prepare a polyphenylene sulfide-based composite material, which exhibits excellent comprehensive performance. On this basis, by adding carbon fiber as a reinforcing agent, a high-strength, low-friction and wear-resistant polyphenylene sulfide-based composite material is prepared at the same time. The present invention has simple technical processes, low manufacturing costs, and good application prospects.

Claims

1. A low-friction and high-wear-resistant resin-based composite material, characterized in that: It is prepared from the following raw materials in parts by weight: 10 to 200 parts of resin matrix, 5 to 80 parts of solid lubricant, and 0 to 60 parts of reinforcing agent; the solid lubricant is a mixture of polytetrafluoroethylene or its derivatives and carbon materials or a mixture of polytetrafluoroethylene or its derivatives and metal derivatives.

2. The low-friction and high-wear-resistant resin-based composite material according to claim 1, characterized in that: It is prepared from the following raw materials in parts by weight: 10 to 200 parts of resin matrix, 5 to 40 parts of polytetrafluoroethylene derivatives, 5 to 30 parts of carbon materials, and 0 to 60 parts of reinforcing agent; Alternatively, it is prepared from the following raw materials in parts by weight: 10 to 200 parts of a resin matrix, 5 to 40 parts of a polytetrafluoroethylene derivative, 5 to 30 parts of a metal derivative, and 0 to 60 parts of a reinforcing agent.

3. The low-friction and high-wear-resistant resin-based composite material according to claim 1, characterized in that: The resin matrix is ​​a thermoplastic resin; The reinforcing agent is glass fiber, aramid fiber, basalt fiber, or carbon fiber.

4. The low-friction and high-wear-resistant resin-based composite material according to claim 3, characterized in that: The resin matrix is ​​polyoxymethylene, polyamide, polysulfone, polyphenylene sulfide, polyetheretherketone or polyimide; The polytetrafluoroethylene derivative is radiation-modified polytetrafluoroethylene, preferably radiation-modified polytetrafluoroethylene nanopowder; The carbon material is graphite, preferably graphite nanopowder; The metal derivative is one or a mixture of two or more of metal sulfide, metal oxide, metal nitride and metal carbide, preferably molybdenum disulfide, more preferably molybdenum disulfide nanopowder; The reinforcing agent is chopped carbon fiber.

5. The low-friction and high-wear-resistant resin-based composite material according to any one of claims 1 to 4, characterized in that: The low-friction and high-wear-resistant resin-based composite material is prepared from the following raw materials in parts by weight: 50 to 75 parts of a resin matrix, 10 to 30 parts of a polytetrafluoroethylene derivative, 10 to 30 parts of a carbon material, and 0 to 20 parts of chopped carbon fibers; Alternatively, the low-friction and high-wear-resistant resin-based composite material is prepared from the following raw materials in parts by weight: 50 to 75 parts of resin matrix, 10 to 30 parts of polytetrafluoroethylene derivatives, 10 to 30 parts of metal derivatives, and 0 to 20 parts of chopped carbon fibers.

6. The low-friction and high-wear-resistant resin-based composite material according to claim 5, characterized in that: The low-friction and high-wear-resistant resin-based composite material is prepared from the following raw materials in parts by weight: 70 parts of a resin matrix, 10 to 20 parts of a polytetrafluoroethylene derivative, and 10 to 20 parts of a carbon material; Alternatively, the low-friction and high-wear-resistant resin-based composite material is prepared from the following raw materials in parts by weight: 70 parts of resin matrix, 10-20 parts of polytetrafluoroethylene derivatives, and 10-20 parts of metal derivatives.

7. A method for preparing the low-friction and high-wear-resistant resin-based composite material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: drying the raw materials, mixing, plasticizing, and drying again to obtain a low-friction and high-wear-resistant resin-based composite material.

8. The method according to claim 7, characterized in that The drying temperature is 60-100°C, and the drying time is 8-16 hours; the plasticizing processing temperature is 200°C-350°C; preferably, the drying temperature is 80°C, and the time is 12 hours; the plasticizing processing temperature is 280°C-300°C.

9. Use of the low-friction and high-wear-resistant resin-based composite material according to any one of claims 1 to 6 in aerospace, transportation electronic devices and mechanical equipment.

10. The use according to claim 9, characterized in that The composite material is used for preparing friction protection parts, low-friction wear-resistant structures, wear-resistant bearings, self-lubricating bearings, and parts of mechanical linings.

Citation Information

Patent Citations

  • PPS / BN composite material with high thermal conductivity and low friction coefficient and preparation method thereof

    CN112094499A

  • Aerogel / polyphenylene sulfide self-lubricating friction material and preparation method thereof

    CN115785671A

  • Polyphenylene sulfide material with low friction coefficient and preparation method thereof

    CN116925547A

  • Low-friction-coefficient dynamic sealing rubber composite material and preparation method thereof

    CN114874555A

  • Poly (phthalazinone) ether resin-based wear-resistant self-lubricating composite material and preparation method thereof

    CN116218219A

Cited By

  • Chemical-resistant wear-resistant carbon fiber reinforced PEEK composite material and preparation method thereof

    CN122060309A